Studies toward the Total Synthesis of Carolacton - Sabitha, Gowravaram; Shankaraiah, K.; Prasad, M. Nagendra; S. Yadav, Jhillu (Synthesis, 2013)
An efficient synthesis of the C1–C19 segment of carolacton is described, starting from d-ribose, (–)-β-citronellene and a homopropargylic alcohol, and which employs a Nozaki–Hiyama–Kishi (NHK) coupling as the key step. Other important steps are cross-metathesis and Evans aldol reactions.
Keywords: carolacton; macrolide; Evans aldol; Nozaki–Hiyama–Kishi coupling; cross-metathesis